Does the Core Capital Requirement Affect Bank Performance? - Julianto; Fitty Valdi ARIE (SEA: Practical Application of Science)
In 2020, the Financial Services Authority of Indonesia (OJK) introduced Regulation No. 12/POJK.03/2020, mandating that all commercial banks maintain a minimum core capital of three trillion rupiah by the end of 2022. This regulatory change aimed to strengthen the financial resilience and stability of the banking sector. However, the potential impact of this requirement on bank performance remains a critical area of investigation. This study seeks to provide empirical evidence on the relationship between core capital requirements and the financial performance of commercial banks in Indonesia. Using banking statistical data from 2013 to 2022, we examine the extent to which core capital influences bank profitability. The study employs Common Equity Tier 1 (CET1) and Capital Adequacy Ratio (CAR) as proxies for core capital, while Return on Assets (ROA) and Return on Equity (ROE) serve as indicators of bank performance. A descriptive-explanatory research design was adopted, and a simple regression analysis was conducted to assess the relationship between these variables. The findings reveal that the core capital requirement has a statistically significant negative effect on bank profitability, suggesting that higher capital requirements may impose constraints on the financial performance of commercial banks. Based on these results, we recommend that banking regulators in Indonesia strengthen their oversight mechanisms and explore strategies to mitigate potential adverse effects, ensuring that capital requirements contribute positively to the stability and long-term performance of the banking sector.